2020
DOI: 10.17352/2455-4634.000045
|View full text |Cite
|
Sign up to set email alerts
|

Bone Quality Obtained in Sinus Lifting with Anorganic Bovine Bone. A CBCT Study

Abstract: Objective: Quantitatively assess bone density in maxillary sinus lifting with ABB (Bio-Oss®), using Cone-Beam computed tomography 6 months after surgery. Material and methods:A retrospective observational study was conducted between February 2018 and February 2019 on 33 Cone-Beam tomographic studies of 29 adult patients of both genders, with maxillary sinus fl oor lift, using Bio-Oss® small particles ( 0.25-1um), large particles (1-2um) or a 50-50 % mix of both, always using Bio-Gide® membranes, in order to me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 23 publications
0
0
0
Order By: Relevance
“…Hounsfield unit (HU) measurement was also performed to evaluate the bone quality on sagittal sections of CBCT scans as proposed by Martinez et al 11 The area of the greatest volume of the bone grafts was determined in a sagittal section. Three measurements with 2 mm vertical distance were made in anterior, middle, and posterior regions of newly regenerated bone mass.…”
Section: Volume Measurementmentioning
confidence: 99%
See 1 more Smart Citation
“…Hounsfield unit (HU) measurement was also performed to evaluate the bone quality on sagittal sections of CBCT scans as proposed by Martinez et al 11 The area of the greatest volume of the bone grafts was determined in a sagittal section. Three measurements with 2 mm vertical distance were made in anterior, middle, and posterior regions of newly regenerated bone mass.…”
Section: Volume Measurementmentioning
confidence: 99%
“…12 Similarly, Melisa et al reported an average bone density of 586±238 HU, a value also corresponding to Type 2-3 bone according to the Lekholm and Zarb classification. 11,12 Residual ridge height is the height of the alveolar bone before the sinus floor augmentation and new bone formation. The height of the ridge increases with the new bone regeneration in the elevated sinus.…”
Section: Casementioning
confidence: 99%